Measurement and analysis of web portal’s performance: a case study in UUM - Rahela Abdul Rahim,; Haslinda Ibrahim,; Sharipah Soad Syed Yahaya,; Khairini Khalid , (Penerbit Universiti Kebangsaan Malaysia, 2010)

(untitled)
The main objective of this study is to develop a generalised system-level model based on queuing system at a system level point of view of web server performance for UUM web portal. A system level performance model views the system being modelled as a ‘black box’ where only the arrival rate and service rate are considered. It is important in order to measure Web server performance metrics such as server utilisation, average server throughput, average number of packet in the server and mean response time. This study refers to infinite population and finite queue. It is a suitable model because it is easy to define and fast to interpret the results yet still represents the real situation